Scientific rationale of ingredients choice for functional fish pastes - A. S. Kupriy; N. I. Dunchenko; E. S. Voloshina (Теория и практика переработки мяса, 2021)
In recent years, the global demand for finished fish products is increased. Aquaculture raw materials are a rich source of nutrients for health. At the same time a large amount of fished fish raw materials are rejected and representing a losses. High-quality raw materials with technological defects are not in demand by the food production of fish products. Perishable substandard fish raw materials can be used in the production of combined fish products. The analysis of the fish catches global scale in the seas, oceans, farmed marine and freshwater aquaculture is carried out. An assessment of the market trends for the production and fish products consumption is made. This article provides an overview of targeted ingredient selection for balanced fish formulations. The characteristics of the most popular plant origin ingredients and their derivatives in the fish pates production are given. A comprehensive assessment of the biological, energy and nutritional value of plant products is given. Described technological approaches and production methods, the safety of vegetable ingredients. The results of research, technological solutions, substantiation of the choice of ingredients adopted by the developers for the formulations of multicomponent pate are summarized. The use of unclaimed raw materials, leftover fish meat with plant ingredients represents additional profit. Fish pate formulations are the basis for the production of complete, ready-to-eat products. Tests of multicomponent fish and vegetable products confirm their high performance. Pates, balanced in nutritional value, minerals, are a finished product that does not require additional preparation. The review article will generate awareness among the researchers, food technologists for the production of fish products and the general public.